Treatment initiation rates of patients with positive anti-hepatitis C virus results in tertiary hospitals in Turkey - Celen, Mustafa K.; Sengel, Buket Erturk; Kaya, Safak; Demirturk, Nese; Azap, Alpay; Pullukcu, Husnu; Mermutluoglu, Cigdem (J Infection Developing Countries, 2024)
Introduction: The aim of this national, multicenter, cross-sectional, retrospective chart review study was to determine the proportion of patients in Turkey who received hepatitis C virus (HCV) treatment after receiving positive anti-HCV results during HCV screening. Methodology: Data related to patients' demographics, laboratory results, time interval from obtaining a positive anti-HCV result to treatment initiation, specialty of the physician requesting anti-HCV screening, and type of hospital were analyzed. Results: Among 1,000 patients who received a positive anti-HCV result, 50.3% were male and 78.5% were screened for HCV-RNA. Among HCV-RNA screened patients, 54.8% (n = 430) had a positive result. Among patients who tested positive for HCV-RNA, 72.8% received HCV treatment in line with their positive anti-HCV results. The median time from obtaining a positive anti-HCV result to initiation of HCV treatment was 91.0 days (interquartile range 42.0 to 178.5). Non -surgical branches requested HCV-RNA testing more frequently than surgical branches (p < 0.001). The rate of access to HCV treatment was higher among patients screened in university hospitals than among patients screened in training and research hospitals (p < 0.001). Conclusions: Our results indicate a higher rate of treatment initiation among patients with HCV infection than is described in the published literature. Furthermore, the time from screening to treatment initiation was considerably shorter compared with other international studies. However, since HCV-RNA testing was not requested in a significant portion of patients with a positive anti-HCV test result, there might be a large patient population with HCV who do not receive treatment.
Keywords: Hepatitis C; anti-HCV; screening; treatment; Turkey